Proceedings of the 2nd International Conference on Data Engineering and Communication Technology ICDECT 2017 - Kulkarni, Anand J.; Satapathy, Suresh Chandra; Kang, Tai.; Kashan, Ali Husseinzadeh; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book features research work presented at the 2nd International Conference on Data Engineering and Communication Technology (ICDECT) held on December 15-16, 2017 at Symbiosis International University, Pune, Maharashtra, India. It discusses advanced, multi-disciplinary research into smart computing, information systems and electronic systems, focusing on innovation paradigms in system knowledge, intelligence and sustainability that can be applied to provide feasible solutions to varied problems in society, the environment and industry. It also addresses the deployment of emerging computational and knowledge transfer approaches, optimizing solutions in a variety of disciplines of computer science and electronics engineering.
Optimization of Constrained Engineering Design Problems Using Cohort Intelligence Method -- Application of Blow Fish Algorithm for Secure Transactions in Decentralized Disruption Tolerant Networks -- A Rig-based Formulation and a League Championship Algorithm for Helicopter Routing in Offshore Transportation -- Music Composition Inspired by Sea Wave Patterns Observed from Beaches -- Multi-Graph Based Intent Hierarchy Generation to Determine Action Sequence -- Modeling Runoff Using Feed Forward-back Propagation and Layer Recurrent Neural Networks -- Discussion on Problems and Solutions in Hardware Implementation of Algorithms for a Car type Autonomous Vehicle -- Obstacle Detection for Auto Driving Using Convolutional Neural Network -- Cryptography Algorithm Based on Cohort Intelligence -- Optimal Rate Allocation for Multi Layer Networks -- Eradication of Rician Noise in Orthopedic Knee MR Images Using Local Mean Based Hybrid Median Filter.
Keywords: Computational intelligence; Telecommunication; Artificial intelligence; Data protection; Computational Intelligence; Communications Engineering, Networks; Artificial Intelligence; Data and Information Security